UJI STRUKTUR BAHAN KAMPAS REM TROMOL PADA KENDARAAN TRUK MITSUBISHI 120 PS MERK MITSUBISHI DAN MERK INDOPARTS - Harjanto, Budi; Wijanarko, Heri; Sukahar (PPM Sdirjianbang Akademi Militer, 2024)
The Mitsubishi 120 PS truck is one of the service vehicles at the Military Academy. This truck is frequently used to transport cadets, particularly to training areas. Given the challenging terrain cadets must navigate, including both uphill and downhill roads, an optimal and consistent braking system is required. This study aims to analyze the wear rate of the drum brake pads used in the Mitsubishi 120 PS truck. The research focuses on determining the hardness, wear rate, and carbon content of the drum brake pads of the Mitsubishi brand compared to the Indoparts brand through hardness, wear, and material composition tests. The test results showed that the hardness of Mitsubishi brake pads is 78.06 kg/mm², which is higher than Indoparts at 58.25 kg/mm². The wear rate for Mitsubishi pads is 5.79x10⁻⁴ mm³/kg.m, which is lower than Indoparts at 1.1599x10⁻³ mm³/kg.m. The carbon content in Mitsubishi pads is 35.48%, higher than Indoparts at 33.18%. This indicates that the harder the brake pad, the lower its wear rate. Therefore, Mitsubishi drum brake pads are more durable and recommended due to their higher resistance to wear.